De novo STXBP1 Mutations in Two Patients With Developmental Delay With or Without Epileptic Seizures - Yang, Ping; Broadbent, Robert; Prasad, Chitra; Levin, Simon; Goobie, Sharan; Knoll, Joan H.; Prasad, Asuri N. (Frontiers in Neurology, 2021)
Objectives: Mutations in the STXBP1 gene have been associated with epileptic encephalopathy. Previous studies from in vitro neuroblastoma 2A cells showed that haploinsufficiency of STXBP1 is the mechanism for epileptic encephalopathy. In this ex vivo study, STXPB1 DNA mutations and RNA expression were assessed from two patients to help understand the impact of STXBP1 mutations on the disease etiology and mechanism. Methods: Microarray analysis and DNA sequencing were performed on two children with development delay, one with and one without infantile spasms. Different pathogenic mutations of STXBP1 were identified in the patients and RNA expression of STXPB1 was then performed by RT-Q-PCR on RNA extracted from blood samples of each patient. Results: Pathogenic deletion [of exons 13–20 and 3′ downstream of STXBP1] and nonsense mutation [c.1663G>T (p.Glu555X) in exon 18 of STXBP1] were detected from the two patients, respectively. RNA analysis showed that 1) the deletion mediated RNA decay, and that 2) no RNA decay was identified for the nonsense mutation at codon 555 which predicts a truncated STXBP1 protein. Significance: Our RNA expression analyses from the patient blood samples are the first ex vivo studies to support that both haploinsufficiency and truncation of STXBP1 protein (either dominant negative or haploinsufficiency) are causative mechanisms for epileptic encephalopathies, intellectual disability and developmental delay. The RNA assay also suggests that escape from nonsense-mediated RNA decay is possible when the nonsense mutation resides <50 nucleotides upstream of the last coding exon-exon junction even in the presence of additional non-coding exons that are 3′ downstream of the last coding exon.